2021
DOI: 10.3390/pharmaceutics13010093
|View full text |Cite
|
Sign up to set email alerts
|

Solid Lipid Particles for Lung Metastasis Treatment

Abstract: Solid lipid particles (SLPs) can sustainably encapsulate and release therapeutic agents over long periods, modifying their biodistribution, toxicity, and side effects. To date, no studies have been reported using SLPs loaded with doxorubicin chemotherapy for the treatment of metastatic cancer. This study characterizes the effect of doxorubicin-loaded carnauba wax particles in the treatment of lung metastatic malignant melanoma in vivo. Compared with the free drug, intravenously administrated doxorubicin-loaded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Multiple delivery strategies have been developed for neoantigens, including synthetic long peptides (SLPs) and nucleic acid (DNA/ mRNA) based vaccines, either through direct injection of unformulated antigens, DC-based autologous transfer, or biomaterial-based delivery system [742]. In a pioneered phase I clinical study, a selected pool of 20 SLPs were SC administered together with adjuvant polyICLC to 6 patients with advanced cutaneous melanoma [743]. These SLPs were shown to induce both CD4 + T cells and CD8 + T cells response [744].…”
Section: Mrna Vaccine Encoding Neoantigen Personalized Vaccinementioning
confidence: 99%
See 1 more Smart Citation
“…Multiple delivery strategies have been developed for neoantigens, including synthetic long peptides (SLPs) and nucleic acid (DNA/ mRNA) based vaccines, either through direct injection of unformulated antigens, DC-based autologous transfer, or biomaterial-based delivery system [742]. In a pioneered phase I clinical study, a selected pool of 20 SLPs were SC administered together with adjuvant polyICLC to 6 patients with advanced cutaneous melanoma [743]. These SLPs were shown to induce both CD4 + T cells and CD8 + T cells response [744].…”
Section: Mrna Vaccine Encoding Neoantigen Personalized Vaccinementioning
confidence: 99%
“…These SLPs were shown to induce both CD4 + T cells and CD8 + T cells response [744]. Four of the six patients were cancer-free 25 months post-treatment, demonstrating the viability of neoantigen vaccination in anticancer treatment [743]. However, peptides have limited immunogenicity, rapid clearance, and different physical-chemical properties restricting their clinical applications [744].…”
Section: Mrna Vaccine Encoding Neoantigen Personalized Vaccinementioning
confidence: 99%
“…In this context, hybrid magnetic nanosystems have enticed researchers’ attention as smart remotely controlled platforms, able to pool together diagnostic, monitoring, and combinatorial therapy features. Over the last decades, advances in the field of theranostics (therapy plus diagnosis) have brought a variety of organic/inorganic hybrid nanocomposites with a high level of integration and complexity, featuring tunable functions strictly related to well-defined architectures. Nevertheless, the integration of diagnostic and therapeutic functionalities in a smart all-in-one platform in the form of hybrid nanocomposites remains a big challenge.…”
Section: Introductionmentioning
confidence: 99%
“…M.L. Fanarraga et al [ 6 ] developed doxorubicin-loaded lipid particles (SLPs) (also known as SLN) for the treatment of lung metastatic malignant melanoma. In this study, the authors conducted comparative in vivo experiments in mice, with intravenous doxorubicin-loaded SLPs and intravenous free drug, and observed that the former significantly reduced the number of pulmonary metastatic foci.…”
mentioning
confidence: 99%